408 Dose-dense paclitaxel and carboplatin plus bevacizumab is an effective and a tolerable first-line regimen for advanced ovarian cancer. (13th November 2020) - Komazaki, H; Takahashi, K; Tanabe, H; Shoburu, Y; Izumi, A; Kamii, M; Tsuda, A; Saito, M; Yamada, K; Takano, H; Niimi, S; Okamoto, A
Abstract : The JGOG 3016 showed that dose-dense paclitaxel and carboplatin (ddTC) improved progression-free survival (PFS) and overall survival (OS) in advanced ovarian cancer (AOC). ICON7 and GOG-0218 showed that bevacizumab (Bev) improved PFS. GOG-0262 suggested that ddTC+Bev showed no superiority in PFS. The aim of this study is to evaluate the efficacy and safety of ddTC+Bev compared with ddTC in AOC. We retrospectively investigated patients with FIGO stage III-IV OC who received ddTC or ddTC+Bev as first-line chemotherapy. PFS was investigated about ddTC+Bev compared with ddTC using log-rank test. Age (<60 vs 60≤), FIGO stage (III vs IV), histological type (serous/endometrioid vs others), initial treatment (primary debulking surgery (PDS) vs neoadjuvant chemotherapy±interval debulking surgery (NAC±IDS)), debulking (complete vs others) and regimen (ddTC+Bev vs ddTC) were investigated by multivariate analysis using cox proportional hazards model to predict prognostic factors. A total of 134 patients were enrolled. Median follow up periods was 30.5 months. 80.1% of patients had stage III disease. 76.7% had serous/endometrioid histologic findings. 59.7% received PDS. 61.9% received complete surgery. Compared with ddTC, ddTC+Bev improved PFS (p<0.01). Multivariate analysis suggested that regimen, histological type, initial treatment, and debulking were independent variable. The frequency of adverse events grade 3/4 of -anemia (p=0.02), -hypertension (p=0.02) and -proteinuria (p<0.01) were higher in ddTC+Bev. ddTC+Bev significantly prolonged PFS. Although the frequency of AE of ddTC+Bev is higher than ddTC, it is totally tolerable. ddTC+Bev is an effective 1st line regimen for AOC.